JET ILA full array and polychromatic operation - Dumortier, P.; Durodié, F.; Jacquet, P.; Lerche, E.; Monakhov, I.; Noble, C.; Puglia, P. (Fusion engineering and design, 2021)
The JET ILA is an Ion Cyclotron Resonance Heating (ICRH) antenna composed of four resonant double loops (RDLs) arranged in a 2 toroidal by 2 poloidal compact array. It has been operated in a range of frequencies from 29 to 51 MHz, but mostly on half array. Some full array pulses were achieved but without all control loops implemented. All control algorithms (first and second stage matching, toroidal and poloidal phasing, totalling 22 feedback loops) have now been implemented and recently allowed to operate the full array at 33 MHz and 42 MHz up to 4 MW. It also allowed for the first time to perform a poloidal phase scan of the antenna at 37 MHz, with dipole toroidal phasing. Although full array operation has mostly proven reliable at 33 MHz, it has proven unstable at 42 MHz in several occasions due to the high level of mutual coupling between the different RDLs inherent to a compact array. To decouple the control of the top and bottom halves, first tests were successfully performed with polychromatic – or dual frequency – operation of the ILA (operation at 2 different frequencies around a central frequency).